Central Pontine Demyelination: A Case Report - Maharjan, Manju; Shrestha, Pranaya; Chandra, Avinash; Maharjan, Jemesh S; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Central Pontine Demyelination is a neurological disease caused by rapidly fl uctuating serum osmolality resulting in severe damage of the myelin sheath of nerve cells in the brainstem, more precisely in the area of pons. This condition is associated with electrolyte disorders, especially severe hyponatremia and its rapid correction. Its clinical course is characterized by alterations in the mental status to debilitating neurological status i.e. coma. Chronic hyponatremia and its correction, with or without evaluating safe limit could result in pontine demyelination. Demyelination might also occur with normal sodium levels, and even if serum sodium levels are corrected within safe limits. The objective of this case report is to give a broad perspective on Central Pontine Demyelination and to discuss about the different factors contributing to the demyelination and the various causes, pathophysiology and the management of this condition. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 99-101